1999
DOI: 10.1093/intimm/11.8.1351
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G-mediated inhibition of antigen-specific cytotoxic T lymphocytes

Abstract: In the present study, we demonstrate that the non-classical MHC class I molecule HLA-G impairs specific cytolytic T cell functions in addition to its well-established inhibition of NK lysis. The antigen-specific cytotoxic T lymphocyte (CTL) response analyzed was mediated by CD8(+) T cells specific for the influenza virus matrix epitope, M58-66, presented by HLA-A2. The transfection of HLA-G1 cDNA in target cells carrying the M58-66 epitope reduced their lysis by these virus-specific CTL. This HLA-G-mediated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 278 publications
(94 citation statements)
references
References 31 publications
1
87
0
6
Order By: Relevance
“…All transfectants were controlled by RT-PCR and Southern blot analysis using specific primers and probes (25). The NK-like YT2C2-PR subclone and the M58 -66 influenza virus matrix peptide-specific CTL line (HC12) were obtained as previously described (21,26). Cells were maintained in RPMI 1640 medium supplemented with 10% inactivated FCS, 2 mM L-glutamine, 1 g/ml gentamicin, and fungizone.…”
Section: Cell Lines and Transfectantsmentioning
confidence: 99%
See 2 more Smart Citations
“…All transfectants were controlled by RT-PCR and Southern blot analysis using specific primers and probes (25). The NK-like YT2C2-PR subclone and the M58 -66 influenza virus matrix peptide-specific CTL line (HC12) were obtained as previously described (21,26). Cells were maintained in RPMI 1640 medium supplemented with 10% inactivated FCS, 2 mM L-glutamine, 1 g/ml gentamicin, and fungizone.…”
Section: Cell Lines and Transfectantsmentioning
confidence: 99%
“…Previous data have shown that the full-length HLA-G1 isoform impairs the lytic activities of both NK and CTL cytotoxic effectors (21,28). To determine whether the truncated HLA-G isoforms, like HLA-G1, were functional molecules with respect to CTL and NK effectors, we conducted chromium release assays using M8 transfected cells as targets.…”
Section: Hla-g2 -G3 and -G4 Isoforms Inhibit The Lytic Activity Of mentioning
confidence: 99%
See 1 more Smart Citation
“…HLA-G molecules inhibit, together with HLA-C and -E, the innate natural killer response against cytotrophoblast cells which lack classical HLA class I and II expression (3)(4)(5). HLA-G antigens affect the adaptative cellular response inducing the apoptosis of cytotoxic CD8 + T lymphocytes (6,7), impairing CD4 + T cell functions and preventing dendritic cell maturation (8,9). HLA-G molecules also induce immunosuppressive regulatory T cell development (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Important factors in the pathogenesis of influenza include the efficient replication of the virus in the respiratory tract and the host immune response, traits that are dependent on each other (4)(5)(6). While the immune response aims to control the spread of the virus, IAV has developed strategies for subverting host defenses, thereby facilitating their spread (7)(8)(9)(10). Further knowledge into how IAV escapes the host immunosurveillance is critical for the design of new treatments that are able to control the disease.…”
mentioning
confidence: 99%